ANALISIS LEGENDA RAWA PENING SEBAGAI SUMBER BELAJAR IPA DI SEKOLAH DASAR - Faida Nurul Karomah; Syarifah Nirmala Kuntum; Agustina Nur Mardianti; Devi Shafia Ningsih; Umi Latifah; Aris Naeni dwiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the folklore of the rawa pening legend as a science learning resource in elementary school. folklore was chosen because it contains local cultural values topics, especially living things,ecosystems, environmental changes, and the formation of lakes or swamps. this study used a qualitative approach with a descriptive analytical method through literatu study and content analysis of the story. the results show that the rawa pening legend can be used as a contextual and interesting science learning medium of elementary students. in the elementary with question-and-answer activities,idenfication of science concepts in the story, group discussions, and simple assignments. these activities help students understand science concepts more mearningfully while also developing learning motivation, critical thinking skills,and appreciation of local wisdom ,therefore, the rawa pening legend is suitable as an alternative learning resource in elementary science education.